Management of Nutritional Services in Regional General Hospitals Drs. Haji Amri Tambunan - Tommy Syahputra Pardede; Chrismis Novalinda Ginting; Karmila Kaban (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Nutrition services are part of medical support services as one of the benchmarks of service quality in hospitals. Nutritional intake of patients is a crucial issue today due to the high prevalence of malnutrition. Good management must be carried out by the nutrition installation so that patients can meet their nutritional needs. The purpose of this study was to determine the description of nutrition service management at the Haji Amri Tambunan Deli Serdang Regional General Hospital. This type of research is qualitative with a case study design. This research was conducted at the Regional General Hospital Drs. Haji Amri Tambunan Deli Serdang. This research was conducted in May and June 2024. The research informants were 8 consisting of the Head of Medical Support as much as 1, Head of Nutrition Installation as much as 1 Administration as much as 2 people and Nutritionists as much as 2 people and nutrition staff as much as 2 people. Data collection was done with indepth interviews, observation and documentation. Data analysis in this study with data reduction, data display, and conclusion drawing. The results of the study can be stated that the management of planning, organizing, implementing, and supervising nutrition services is in accordance with the SOP. Internal factors that support are standard operating procedures, and internal factors that hinder are human resources. External factors are cooperation with outside parties. From the results of the study it can be concluded that the management of nutrition services has been running well. It is recommended that the Nutrition installation of Drs, Haji Amri Tambunan Deli Serdang General Hospital can increase human resources so that no officers do double work and change the food menu should not be less than 10 days to avoid saturation of patients in consuming food. Keywords: Planning, Organizing, Implementation, Supervision, Nutrition Service Management